The collected works of Henrik Ibsen. - Ibsen, Henrik, 1828-1906.; Archer, William, 1856-1924. (London, W. Heinemann, 1908)
v.1. Lady Inger of Ostrat. The feast at Solhoug. Love's comedy.--v.2. The Vikings of Helgeland. The Pretenders.--v.3. Brand.--v.4. Peer Gynt.--v.6. The league of youth. Pillars of society.--v.7. A doll's house. Ghosts.--v.8. An enemy of the people. The wild duck.--v.9. Rosmerholm. The lady from the sea.--v.10. Hedda Gabler. The master builder.--v.11. Little Eyolf. John Gabriel Borkman. When we dead awaken.--v.12. Henrik Ibsen, by Edmund Gosse. Mode of access: Internet. 2